Classification of different magnetic structures from image data using deep neural networks - Ibn Hasib, Fahad; Swarna, Nakiba Farhana (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2021.